Effects of heterodox populist policies in the private sector: The Argentine experience (2004-2016) - Diego G. Fano; Victor A. Lucero; Antonio Marín (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2018)
This study describes the effects of heterodox fiscal and monetary policies pursued by Argentina, associated with existing populist governments since 2004. Argentina's fiscal policy was characterized by increased public expenditures and the tax burden. The further expansion of public expenditure led to fiscal deficits that were financed by money creation, thereby triggering an inflationary process that, up to date, could not be controlled. In turn, the loss of value of the local currency led to a process of exodus of capital, which tried to be contained using exchange controls and restrictions, popularly known as "cepo cambiario" (dollar exchange clamp). The side effect of it was a significant overvaluation of the real exchange rate. In order to study the effects of these measures in private companies, the financial statements of 148 companies (that make public offer of shares in the stock market, with public financial statements) were analyzed, belonging to the sectors of construction, agriculture, food and oil industries, as well as 25 banks and financial institutions. It was observed that, in general, government policies significantly affected the profitability levels and investment rates for private companies, deteriorating margins and discouraging investment. In turn, banks and financial enterprises accompanied the rise of inflation with rising interest rates and declining loans to the productive and real estate sector, shifting its portfolio to finance short-term consumption. The results of this study can confirm the harmful effects of populist and heterodox policies over the real economy, especially related to the long-term effects associated with the loss of the investment.
Keywords: 330